Residual N-Total and P-Available in the Rizosphere of Arachis hypogaea L. at Various Soil Moisture Content Fertilized by Mushroom Baglog Compost - Fanylaila Safitri; Lolita Endang Susilowati; Sutriono (Jurnal Biologi Tropis, 2023)
Groundnut growth and production can be increased by fertilizing. One indicator used to measure nutrient availability is residual N-total and P-available in the rhizosphere. Environmental factors such as soil moisture can affect the level of residual N-total and P-available in peanut rhizosphere. The aim is to determine the effect of Baglog Compost on residual total Nitrogen and available Phosphate at various levels of soil moisture. The method used in this research is an experimental method with a complete randomized design (RAL) 3x2 factorial. The results showed that the highest N-total and P-available content was obtained in PB4 treatment (100% field capacity) 0.67% which was given mushroom baglogs. Giving mushroom baglogs at various soil moisture levels has a significant effect on soil N-total, soil C-organic, soil CEC, and soil P-available parameters except for soil pH parameters.